AI-Enhanced Personalized Learning Practices in Higher Engineering Institutes - Rajesh, K.; Sivapragasam, C.; Dargar, Shashi Kant (Journal of Engineering Education Transformations, 2025)
The main task of engaging the students with an interesting classroom environment is challenging in nature. The better way of teaching the students with effective learning pedagogy seems to be more effective. In this technological era, every student requires some technological involvement in their day-to-day process. So, with a broadcasted mindset, an active learning pedagogy has been initialized in this manuscript which gives more and more active methods of learning especially for engineering students. This research mainly focuses on a widely available learning process that is more effective in context with an easy understanding of the concepts. The AI – Enhanced Personalized learning methodology has been utilized in this manuscript. A deep understanding of the concept lies in the visual representation of the concept. In context to this, the simulation-based active learning pedagogy has been implemented for the Electrical Engineering graduates of the third year. The pedagogy related cource outcome (CO) has been framed. The effectiveness of the implemented method has been evaluated with various feedback responses and their scores in the end-semester with and without AI methodology help to view the performance metrics of the implemented AI – based learning learning pedagogy. Surely, this method yields good results in the performance of every student.